PRINSIP KESATUNAN DALAM ACARA CURAHAN HATI PEREMPUAN DI TRANS TV EPISODE JUNI 2016 - Sally Dwi Andari (Jurnal Pembahsi (Pembelajaran Bahasa Dan Sastra Indonesia), 2017)
Abstract:This study aims to identify and describe the principles of politeness and maxims dominant. This study used descriptive qualitative method. Data sources are the host and speakers, containing data in the form of speech politeness principle, data collection techniques using techniques see, record and record, namely data analysis techniques of data analysis techniques Chaer. The results of this study are 149 utterances covering 41 speech emcee containing 24 speech politeness principle and resource containing politeness principle. Speech emcee dominant maxim is the maxim of praise (36.58%) and the speech resource that is the maxim of humility (41.66%).